The Influence of External and Internal Factors on Banking Profitability Before and During the Covid-19 Pandemic - Rizal Indra Tjahya; Jasman, Jasman (Formosa Journal of Multidisciplinary Research, 2024)
The Covid-19 pandemic is putting strong pressure on the Indonesian economy, including national banking. This research design uses quantitative methods with explanatory techniques. This research aims to examine the influence of external factors (BI Rate, Inflation, and Exchange Rate) and internal factors (Capital Adequacy Ratio, Non-Performing Loans, Loan Deposit Ratio, and Operating Expenses Operating Income) on the profitability (Return On Equity) of conventional commercial banks before and during covid-19. The data collection technique used purposive sampling with a sample size of 24 banks and 240 observations before and during COVID-19. Data testing and analysis used panel data regression analysis and performed different tests. The results of data analysis and testing show that the BI Rate, Inflation, Exchange Rate, NPL, and LDR do not influence ROE both before and during Covid-19, meanwhile, CAR and BOPO have a negative and significant effect on ROE both before and during Covid-19. The results of different tests show significant differences in the BI Rate, Inflation, Exchange Rate, CAR, and LDR before and during COVID-19, while there are no significant differences in NPL and BOPO either before or during COVID-19.